Epidemiological profile of ocular morbidities in age group of 20 year and above at field practice area of rural health training center: a cross sectional study - Rajput, Rupali R.; Pawar, Shashikant R. (International Journal Of Community Medicine And Public Health, 2018)
Background: Ocular morbid conditions are responsible for partial or total blindness. Blindness due to ocular morbidities with its economic and social consequences represents a serious public health problem in different region of the world. According to the World Health Organization; 285 million people are estimated to be visually impaired worldwide: 39 million are blind and 246 million have low vision. The study has to be done to determine the prevalence of blindness and common ocular morbidities in age groups of 20 years and above and to study the distribution patterns of ocular morbidities among different socio-demographic conditions. Methods: The present cross-sectional study was conducted to find the prevalence of blindness and other ocular morbidities among adult population of 20 years and above, and also to study determinants of ocular morbidities. Results: Prevalence of blindness was found to be (2.33%) and prevalence for ocular morbidities was found to be (36.84%) in the population with a marginal higher prevalence in females (38.72%) as compared to the males (34.98%).In present study, out of 600 study subject, 221 (36.84%) suffered ocular morbidities. The major cause of morbidities was refractive errors (53.39%), followed by cataract (35.74%), conjunctivitis (1.80%). The prevalence of ocular morbidities in the age group 20-29 year was 11.12%, then it increases significantly (p<0.01) with advancing age to 74.21% in the age group of ≥60 years. Conclusions: Increasing age showed increasing prevalence of ocular morbidity. Widows/widower, Hindu religion, Individuals from nuclear family, skilled worker showed higher prevalence of ocular morbidity.